Study on articular surface morphology of atlantoaxial lateral mass based on differential manifold - Zhang, Zeyuan; Zhao, Yao; Chou, Dean; Zhang, Shuhao; Zhou, Ruifang; Ma, Zeyu; Wang, Limin; Yu, Zhong; Liu, Yilin; Wang, Yuqiang (Journal of orthopaedic surgery and research, 2023)
Objectives To propose a surface reconstruction algorithm based on a differential manifold (a space with local Euclidean space properties), which can be used for processing of clinical images and for modeling of the atlantoaxial joint. To describe the ideal anatomy of the lateral atlantoaxial articular surface by measuring the anatomical data. Methods Computed tomography data of 80 healthy subjects who underwent cervical spine examinations at our institution were collected between October 2019 and June 2022, including 46 males and 34 females, aged 37.8 [+ or -] 5.1 years (28-59 years). A differential manifold surface reconstruction algorithm was used to generate the model based on DICOM data derived by Vision PACS system. The lateral mass articular surface was measured and compared in terms of its sagittal diameter, transverse diameter, articular surface area, articular curvature and joint space height. Results There was no statistically significant difference between left and right sides of the measured data in normal adults (P > 0.05). The atlantoaxial articular surface sagittal diameter length was (15.83 [+ or -] 1.85) and (16.22 [+ or -] 1.57) mm on average, respectively. The transverse diameter length of the articular surface was (16.29 [+ or -] 2.16) and (16.49 [+ or -] 1.84) mm. The lateral articular surface area was (166.53 [+ or -] 7.69) and (174.48 [+ or -] 6.73) mm.sup.2 and the curvature was (164.03 [+ or -] 5.27) and (153.23 [+ or -] 9.03)[degrees], respectively. The joint space height was 3.05 [+ or -] 0.11mm, respectively. There is an irregular articular space in the lateral mass of atlantoaxial, and both upper and lower surfaces of the articular space are concave. A sagittal plane view shows that the inferior articular surface of the atlas is mainly concave above; however, the superior articular surface of the axis is mainly convex above. In the coronal plane, the inferior articular surface of the atlas is mostly concave above, with most concave vertices located in the medial region, and the superior articular surface of the axis is mainly concave below, with most convex vertices located centrally and laterally. Conclusion A differential manifold algorithm can effectively process atlantoaxial imaging data, fit and control mesh topology, and reconstruct curved surfaces to meet clinical measurement applications with high accuracy and efficiency; the articular surface of the lateral mass of atlantoaxial mass in normal adults has relatively constant sagittal diameter, transverse diameter and area. The distance difference between joint spaces is small, but the shape difference of articular surfaces differs greatly. Keywords: Articular surface of lateral atlantoaxial mass, Craniocervical junction abnormalities, Differential manifold, Atlantoaxial fusion apparatus